2011
DOI: 10.1002/cncr.26032
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic and staging implications of bone invasion in oral squamous cell carcinoma

Abstract: BACKGROUND: A study was undertaken to determine whether bone invasion is an independent prognostic factor in oral squamous cell carcinoma (SCC) after taking into account the extent of bone invasion. METHODS: The study was a retrospective review of 498 patients with oral SCC undergoing surgery with curative intent, 102 of whom had pathologically proven bone invasion. Bone invasion was categorized as absent, cortical, or medullary and tested for association with disease control and survival. RESULTS: After adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
102
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(111 citation statements)
references
References 11 publications
6
102
2
1
Order By: Relevance
“…We previously reported that patients who have T4 oral SCC with medullary invasion have significantly decreased OS and DSS because of distant, rather than locoregional, failures. 24 This study includes a subgroup of patients who had previously been diagnosed with and undergone treatment for another head and neck SCC, including radiotherapy. We have not excluded these patients, because the effect of their prior treatment on their outcome in this study is not known.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that patients who have T4 oral SCC with medullary invasion have significantly decreased OS and DSS because of distant, rather than locoregional, failures. 24 This study includes a subgroup of patients who had previously been diagnosed with and undergone treatment for another head and neck SCC, including radiotherapy. We have not excluded these patients, because the effect of their prior treatment on their outcome in this study is not known.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year disease-specific survival rate was 61% for patients with mandibular invasion, compared to 80% for those without. Recently, Ardalan and his colleagues published another retrospective review, with a larger sample of 498 patients, 102 of whom had histologically proven invasion of bone at initial surgery [13]. After adjusting for other factors in a multivariate analysis, medullar invasion was the only independent predictor of reduced survival.…”
Section: Introductionmentioning
confidence: 95%
“…There is some evidence to suggest that the prognosis of T4 tumors with bone invasion varies substantially according to tumor size, and small primary tumors with bone invasion are associated with a relatively favorable prognosis that does not warrant T4 classification. 32,33 Further study is required to confirm whether incorporation of DOI data is necessary for tumors in these subsites, particularly after reclassification of tumors with bone invasion based on consideration of tumor size. This study has several limitations.…”
mentioning
confidence: 97%